Integrasi Pendidikan Multikultural dalam Pembelajaran Matematika: Tren, Praktik, dan Implikasinya terhadap Literasi Numerasi Abad ke-21 Sebuah Systematic Literature Review - Dewi Sartika; Lisda Ramdhani; I Made Pageh; I Putu Sriartha; Wayan Mudana (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyses the trends, practices, and implications of integrating multicultural education into mathematics learning to strengthen 21st-century numeracy literacy through a Systematic Literature Review (SLR) approach. Contemporary mathematics education faces global demands to deliver learning that not only emphasizes cognitive achievement but is also sensitive to cultural diversity, responsive to technological advancement, and relevant to modern life. Ethnomathematics, digital literacy, multiliteracies, and culturally responsive pedagogy have emerged as key components increasingly integrated into mathematics instruction to enhance creativity, critical thinking skills, numeracy literacy, and active student engagement. This review examined 23 articles published between 2018 and 2025 related to ethnomathematics, multicultural pedagogy, numeracy literacy, and educational technology. The findings indicate that integrating multicultural education significantly strengthens conceptual understanding, promotes higher-order thinking skills (HOTS), supports the development of students’ cultural identity, and increases motivation and learning engagement. Ethnomathematics has proven effective as a bridge connecting formal mathematical concepts with local cultural practices, while the use of technologies such as e-learning platforms, mobile modules, and digital media enables more contextual, adaptive, and inclusive learning environments. However, several gaps were identified in the existing literature. First, most studies remain fragmented, focusing separately on ethnomathematics or digital literacy without proposing a comprehensive integrative framework that systematically combines multicultural, numeracy, and technological dimensions within mathematics learning. Second, longitudinal studies examining the long-term impact of multicultural approaches on 21st-century numeracy literacy outcomes are still limited. Third, cross-cultural and cross-educational-level comparative research remains scarce, restricting the generalizability of findings across diverse contexts. Therefore, further research is needed to develop holistic conceptual and practical models that reinforce the strategic role of multicultural mathematics education in preparing numerate, inclusive, and globally adaptive generations.